2018
DOI: 10.1016/j.hpb.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

“Apple Far from the Tree”: comparative effectiveness of fiberoptic single-operator cholangiopancreatoscopy (FSOCP) and digital SOCP (DSOCP)

Abstract: DSOCP system provides enhanced diagnostic yield, shorter procedure times and less radiation exposure compared to FSOCP system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 27 publications
(34 reference statements)
1
33
0
Order By: Relevance
“…Ducts were completely cleared (technical success) in 97.3% of patients and cleared in a single session in 77.4% of patients . The results corroborate previously published studies on D‐SOC in the management of difficult‐to‐treat bile duct stones . The overall success rate of stone removal with D‐SOC appears to be over 95%.…”
Section: Therapeutic Cholangioscopic Proceduressupporting
confidence: 84%
See 1 more Smart Citation
“…Ducts were completely cleared (technical success) in 97.3% of patients and cleared in a single session in 77.4% of patients . The results corroborate previously published studies on D‐SOC in the management of difficult‐to‐treat bile duct stones . The overall success rate of stone removal with D‐SOC appears to be over 95%.…”
Section: Therapeutic Cholangioscopic Proceduressupporting
confidence: 84%
“…The D‐SOC could be used in a fluoroscopy/radiation‐free setting to accomplish successful bile duct treatment without the usual exposure to radiation and other disadvantages of the fluoroscopy setting . D‐SOC appears to be superior to SOC with a higher rate of stone clearance in the first procedure (83% vs 58%, P < 0.01) with a shorter procedure time (49 vs 57 min, P = 0.032) . In case of intrahepatic stones, the thinner LL probe is generally preferred to the EHL probe.…”
Section: Therapeutic Cholangioscopic Proceduresmentioning
confidence: 99%
“…Baseline characteristics of the studies are presented in Table . Fourteen studies reported procedure duration . Median duration was 68.7 min, ranging from 30 min to 165 min.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the PRISMA flow diagram of selected studies. Of the 24 studies evaluated, 13 were carried out in America, 12,14,15,[17][18][19]21,22,25,26,30,31,35 seven in Asia, 13,20,23,24,27,29,34 three in Europe, 16,28,33 and one was a multinational study spanning America, Asia, and Europe. 32 Ten studies were multicenter.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation